Fuzzy soft Γ-ring - Onar, S.; Ersoy, B. A.; Tekir, U. (SPRINGER INT PUBL AG, 2012)
The concept of fuzzy soft Gamma-ring is introduced; and some properties of fuzzy soft Gamma-rings are given. Then the definitions of fuzzy soft Gamma-ideals are proposed and some of their theories are considered.
Keywords: Gamma - ring; fuzzy soft ring; soft ring; SETS; Science & Technology - Other Topics